The Implementation of Risk Management, Internal Control Systems, and Audits’ Role’s Effects on Credit Policy - Azita, Nabila Nurrachmatika (Interdisciplinary Social Studies, 2021)
Background: The current government expects progress in economic equality and national development. In national development will certainly require very large funds, therefore the role of the bank is absolute.Aim: This research aims to analyze the influence of risk management, the effectiveness of internal control systems, and the role of internal audits on credit policy.Method: This study uses survey methods from the results of previous research. The testing method is done using multiple linear regression causal analysis.Findings: The results of this study show that the role of risk management, internal control systems and internal audits has an influence on credit policy.